2021
DOI: 10.3390/toxics9090220
|View full text |Cite
|
Sign up to set email alerts
|

A Glyphosate-Based Formulation but Not Glyphosate Alone Alters Human Placental Integrity

Abstract: Glyphosate (G)-based herbicidal formulations, such as the most commonly used one, Roundup (R), are major pesticides used worldwide on food and feed. Pregnant women may be frequently exposed to R compounds. These are composed of G, which is declared as the active principle, and other products contained in formulations, named formulants, which have been declared as inerts and diluents by the manufacturers. These formulants have, in fact, been demonstrated to be much more toxic than G, in particular to placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An ex vivo human perfusion system experiment was carried out to analyze whether the placenta is permeable to G (33.8 mg/L). Caffeine and benzoic acid were reported to transfer throughout the perfusion system more easily than G. Only 15% of G crossed the placental barrier to reach the fetal circulation, with a very low permeability coefficient compared with caffein and benzoic acid [81]. Finally, a recent study on placental perfusion ex vivo from human full-term placenta analyzed the difference between G alone (1 ppm) and R formulation containing formulants such as POEA (1 ppm G equivalent) [82].…”
Section: Placentamentioning
confidence: 99%
“…An ex vivo human perfusion system experiment was carried out to analyze whether the placenta is permeable to G (33.8 mg/L). Caffeine and benzoic acid were reported to transfer throughout the perfusion system more easily than G. Only 15% of G crossed the placental barrier to reach the fetal circulation, with a very low permeability coefficient compared with caffein and benzoic acid [81]. Finally, a recent study on placental perfusion ex vivo from human full-term placenta analyzed the difference between G alone (1 ppm) and R formulation containing formulants such as POEA (1 ppm G equivalent) [82].…”
Section: Placentamentioning
confidence: 99%
“…In fact, mass spectrometry analyses of mixtures of pure, usable, commercially available formulations of pesticides revealed hundreds of unidentified compounds spread over Gauss curves [ 4 ], indicating that adjuvants are not only variable and numerous but also contain residual chemicals. More importantly, these make mixtures hundreds to thousands of times more efficient with respect to oxidative stress in vivo and in patients, as demonstrated in court during the Monsanto Affair, or in human placentas [ 6 ] than what is expected from the sole ADI of the purified declared ingredient in the long term that serves as basic data. This insufficiency in assessing chronic effects was confirmed by detailed omics studies in vivo [ 7 , 8 ].…”
mentioning
confidence: 99%
“…[11][12] Several studies have indicated that GLY can reach the developing embryo, inducing toxic effects, since is able to diffuse through the placenta. [23][24][30][31][32] In agreement, GLY exposure in rats, during perinatal phases, results in neurobehavioral, estrogenic, and thyroid hormone alterations in offspring. [33][34][35][36] Considering the extensive use of GBH, it is relevant to evaluate the effect of formulations, particularly when the exposure occurs during development.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have indicated that GLY can reach the developing embryo, inducing toxic effects, since is able to diffuse through the placenta 23–24,30–32 . In agreement, GLY exposure in rats, during perinatal phases, results in neurobehavioral, estrogenic, and thyroid hormone alterations in offspring 33–36 .…”
Section: Discussionmentioning
confidence: 70%